A Gerontology Practitioner Continuing Education Certificate Program: Lessons Learned. Issue 4 (7th August 2016) - Englehardt, Jacqueline; Hash, Kristina M.; Mankowski, Mariann; Harper-Dorton, Karen V.; Pilarte, Ann E.
ABSTRACT: This article discusses the results of a school of social work survey assessing the geriatric training needs of social workers and other professionals in aging and the need for a gerontology practitioner's continuing education (CE) certificate program. A total of 391 professionals, the majority of whom were social workers, participated in an online needs assessment survey. Of all respondents, the majority (77%) expressed some interest in enrolling in a certificate program within 2 years. Increased knowledge and competence, personal satisfaction and growth, and meeting CE requirements for professional licensure renewal were the major reasons given for interest in enrollment. Cognitive changes, dementia, and end-of-life issues were each selected by almost half of the respondents as areas in which they felt they needed the most training. Legal issues, health care, and social policies and programs were also of interest. In response to survey findings, a 100-clock-hour program was developed to strengthen the skills of persons who work with older adults. The emphasized curricular areas included understanding aging processes and social and economic issues confronting older persons. Related programs, seeking to assess the geriatric training needs of professionals in efforts to develop an appropriate educational program to respond to these needs, can benefit from challenges and lessons learned from this interdisciplinary CE program development.